2020
DOI: 10.1093/europace/euaa289
|View full text |Cite
|
Sign up to set email alerts
|

Multi-catheter cryotherapy compared with radiofrequency ablation in long-standing persistent atrial fibrillation: a randomized clinical trial

Abstract: Aims Restoring sinus rhythm (SR) by ablation alone is an endpoint used in radiofrequency (RF) ablation for long-standing persistent atrial fibrillation (AF) but not with cryotherapy. The simultaneous use of two cryotherapy catheters can improve ablation efficiency; we compared this with RF ablation in chronic persistent AF aiming for termination to SR by ablation alone. Methods and results Consecutive patients undergoing thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…Due to the difficulty of anticipating clinical incidence precisely, similar sample sizes have been applied to several clinical trials. 21 , 22 Although the interpretation of the data is limited, these findings still show the real outcomes of daily ablation practice and confirm the results of previous trials. Large-scale randomized clinical trials are demanded to further confirm the conclusions of this study.…”
Section: Discussionsupporting
confidence: 84%
“…Due to the difficulty of anticipating clinical incidence precisely, similar sample sizes have been applied to several clinical trials. 21 , 22 Although the interpretation of the data is limited, these findings still show the real outcomes of daily ablation practice and confirm the results of previous trials. Large-scale randomized clinical trials are demanded to further confirm the conclusions of this study.…”
Section: Discussionsupporting
confidence: 84%
“…Previous randomized study on multicatheter cryoablation showed that cryotherapy can be used to deliver linear lesions in the left atrium comparable to RF, but long-term outcomes were not significantly different, and so further study of this method using standard cryo-catheters was not recommended. 76 Ultra-low-temperature cryotherapy (Adagio Medical, Laguna Hills, CA) may change the limitations associated with standard cryotherapy. It is a novel and advanced form of cryotherapy that has begun its initial clinical evaluations.…”
Section: Alternative Ablation Methods: Future Applicationsmentioning
confidence: 99%
“…Previous randomized study on multicatheter cryoablation showed that cryotherapy can be used to deliver linear lesions in the left atrium comparable to RF but long-term outcomes were not significantly different and so further study of this method using standard cryo-catheters was not recommended. 80 temperatures (down to -196 degrees Celsius), an esophageal warming balloon is used in the company's protocol for left atrial ablation work. The main published clinical evaluation using this technology so far, has been to treat atrial flutter.…”
Section: Ultra-cryotherapymentioning
confidence: 99%
“…Cryotherapy is comparable in efficacy to RF methods, but usually involves the use of contrast agents. [ 76 ] RF ablation without contrast and with meticulous control of arterial pressure is the preferred method.…”
Section: Managing Arrhythmia In Renal Diseasementioning
confidence: 99%